Optimization of syngas production via methane bi-reforming using CeO2 promoted Cu/MnO2 catalyst - Ibrahim I.H.; Shafiqah M.-N.N.; Rosli S.N.A.; Mohamed H.; Panpranot J.; Cuong Nguyen V.; Abidin S.Z. (Institution of Chemical Engineers, 2025)
Currently, syngas plays an important role in renewable and sustainable energy production. The idea of manufacturing syngas via bi-reforming methane, which involves the combination of methane (CH4), carbon dioxide (CO2), and steam, appears very promising. As a result, the goal of this research is to improve syngas output by improving process parameters in methane bi-reforming using a 3%Ce-15%Cu/MnO2 catalyst. Optimization analysis was performed using response surface methodology (RSM). The ultrasonic impregnation (UI) method was employed to synthesize the catalysts used in this study. Following that, the catalyst was characterized using several techniques such as Brunauer-Emmett-Teller (BET), X-ray diffraction (XRD), temperature programmed reduction (TPR), temperature programmed desorption (TPD), and temperature programmed oxidation (TPO). The findings of the characterization show that the presence of CeO2 promoters has a dual effect on the size of CuO crystallites. Firstly, it reduces the size from 19.07 nm to 13.66 nm because to the dilutive effect generated by the inclusion of CeO2. Second, the presence of CeO2 promoter accelerates the transition from CuO to Cu0 metallic phase. Furthermore, the addition of CeO2 boosts the CH4 and CO2 conversion rates by 23.65% and 24.93%, respectively. As a result, the H2 yield increases significantly when compared to the unpromoted catalyst. The study investigates the influence of process parameters, specifically the reaction temperature (700?900?), CO2 ratio (0.2?1), and gas hourly space velocity (GHSV) (16?36 L g cat?1 hr?1), on the conversion of CH4 and CO2, as well as the H2/CO ratio. The optimization study finds that the highest conversion rates for CH4 and CO2 are 78.32% and 72.45%, respectively, when the reaction temperature is 800 C, the CO2 ratio is 0.6, and the gas hourly space velocity (GHSV) is 26 L g cat?1 hr?1. The optimum conditions result in the highest syngas ratio of 1.77. The results of the optimization are then assessed using the mean errors. The H2/CO ratio, as well as the average errors for CH4 and CO2 conversions, are discovered to be 0.15%, 0.95%, and 0%, respectively. ? 2024 Institution of Chemical Engineers